Synthesis and characterization of NI(II), CU(II) and ZN(II) coordination polymers and the applications in electrochemical studies and adsorption of DYES / Bibi Sherino - Bibi , Sherino (2018)
This work describes the synthesis and characterization of benzylimidazole and piperazine based coordination polymers with two different linkers (adipic acid (A) and terephthalic acid (T)) namely: TBim-Ni-CP (a), TBim-Cu-CP (b), TBim-Zn-CP (c), ABim-Ni-CP (d), ABim-Cu-CP (e), ABim-Zn-CP (f), TP-Ni-CP (g), TP-Cu-CP (h), TP-Zn-CP (i), AP-Ni-CP (j), AP-Cu-CP (k), AP-Zn-CP (l). The physical and chemical characterization of these coordination polymers have been studied by elemental analysis, Fourier transform infrared spectrometry, single crystal and powder X-ray diffraction, BET surface area analysis, thermogravimetric analysis and electrical impedance spectroscopy for conductivity analysis. The synthesized coordination polymers were used as a modifier for carbon paste electrode to study the electrochemical behaviour of ferricyanide. Electrochemical characterization revealed that the newly synthesized coordination polymers have excellent potential as electrode modifier for the redox reaction of ferricyanide. The redox reaction of ferricyanide was reversible and diffusion controlled and the calculated diffusion coefficient values were in the range of 1.89-5.96 ×10-5 cm2 s-1. BET and conductivity measurements showed that AP-Ni-CP has large pore size of 361.57 Å and high conductivity of 1.28×10-3 S/cm compared to other coordination polymers. Therefore, AP-Ni-CP was selected as electrochemical sensor to study the electrochemical detection of H2O2. Systematic optimization procedures were carried out for AP-Ni-CP/CPE by cyclic voltammetry and chrono-amperometry methods. Under optimized condition AP-Ni-CP/CPE response was linear for H2O2 in the concentration from 0.004 to 60 mM with the limit of detection of 0.0009 mM. The effect of interfering species on the reduction peak current response show a minor change of signals (>5%). The modified electrode has good repeatability due to lifetime stability. AP-Ni-CP/CPE electrode was also applied in real samples (lens cleaner solution) for the detection of H2O2 with the recoveries of 94.7 to 107%. The application of the synthesized coordination polymers has been extended to adsorption study. Adsorption behaviour of the synthesized coordination polymers towards two oppositely charged dyes (Methylene Blue and Chicago Sky Blue) were explored through batch method by UV–vis spectrophotometer. Comparison study of adsorption of dyes show that coordination polymers were more selective toward anionic dyes Chicago Sky Blue (CSB) compared to cationic dye Methylene Blue (MB) due to the presence of cationic groups in coordination polymers. The % removal for CSB and MB are in the range of 65-95% and 4-48 % respectively. ABim-Zn-CP (f) was selected for the kinetic and isotherm study of CSB and MB due to it good % removal towards both dyes. Adsorption parameters, including adsorbent dosage, pH of solution, dye concentration, and time were optimized. ABim-Zn-CP has excellent percentage capacity of 144.26 mg/g and 174.64 mg/g for CSB and MB respectively. Kinetics studies indicated that the synthesized adsorbent ABim-Zn-CP (f) followed the pseudo-second order rate model with R2 value 0.991 and 0.993 respectively, for CSB and MB. The Langmuir isotherm with high R2 value as compared to Freundlich isotherm indicated that CSB and MB adsorption for the synthesized coordination polymer follows monolayer adsorption. The adsorbent also has excellent potential application in environmental water sample with recovery of 98% for mixture of both dyes.